The Effectiveness of Learning the “Tari Merak” Using Youtube Media in Online Learning - Tania, Eva; Muktiarni, M; Mupita, Jonah (Jurnal Abdimas Kartika Wijayakusuma, 2021)
The challenges of the world of education in meeting the needs of the millennial generation are quite large. This is due to their different life experiences, especially the experience of using communication technology. With the Covid-19 pandemic, learning is required to take place online. One form of learning is the practice of dance, one of which is the Tari Merak. With a variety of movements, learning the Tari Merak can be done online using Youtube as a learning tool. Youtube is one of the social media with video access. Its users can access, archive, and show videos, so the benefits of Youtube are very large in this pandemic period because it can facilitate practical learning. This paper describes the activities of 2021 KKN Tematik MDBPE-MBKM 2021 which will be carried out at SMPN 1 Subang starting on August 30, 2021 until September 1, 2021. The approach used in this activity is a quantitative approach with a pre-experimental design method of type one group pretest-posttest. The results of the study showed that the average posttest score of students was 76.25%, which was greater than the average pretest score of 36.15%. Thus, there is an increase in understanding of 40.10% of the learning process of Tari Merak material through Youtube media.